Construction relationship between a functionally graded structure of bamboo and its strength and toughness: Underlying mechanisms. (23rd May 2023) - Han, Shanyu; Xu, Haoqian; Chen, Fuming; Wang, Ge
Highlights: Quantitative analysis of the distribution law of bamboo properties. The mechanism of bamboo strength and toughness revealed. A new device for in situ electron microscopy is used. Abstract: The special functional gradient structure of bamboo determines its excellent properties of strength and toughness, which make it an excellent candidate for biomimicking purposes in advanced material design. However, the construction relationship and underlying mechanism of the functionally graded structure in the direction of the bamboo wall and its excellent strength and toughness have not been elucidated. Accordingly, this study first conducts a quantitative analysis of the relationship between the directional gradient structure of the bamboo wall layer and its chemical composition and physical and mechanical properties. To this end, in situ scanning electron microscopy ( in situ SEM) was used to investigate the mechanical behavior and failure mode of the bamboo wall layer under the effect of external loads, and to investigate the structure–activity relationship between the gradient structure of the bamboo wall layer and its strength and toughness, as well as the potential mechanism of action. From the perspective of structural mechanics, the mechanical model of the bamboo wall direction under the applied load was analyzed, and the mechanism by which the bamboo wall gradient structure improves the strength and toughness of bamboo was further elucidated. The results showed that the uniform gradient distribution of the vascular bundles and their interfaces in the direction of the bamboo wall determines the gradient distribution of its chemical components and physical and mechanical properties. Together, the uneven deformation of parenchyma cells and fibers, multi-path propagation of cracks, fiber bridging, pull-out and fracture constitute the mechanism by which the bamboo gradient structure contributes to its strength and toughness. This study provides a theoretical basis and innovative ideas for the design of biomimetic advanced materials based on the bamboo wall gradient structure by revealing the potential close relationship between the excellent mechanical properties of bamboo of high strength and toughness and its functional gradient structure.